Extended Abstracts of the 2005 International Conference on Solid State Devices and Materials 2005
DOI: 10.7567/ssdm.2005.c-10-4
|View full text |Cite
|
Sign up to set email alerts
|

Highly Manufacturable Hf-silicate Technology with Optimized Composition for Gate-First Metal Gate CMOSFET

Abstract: Effects of composition in Hf-silicate are evaluated for CMOSFET with TiN gate. Higher k value can be achieved by reducing Si content, effective to improve EOT-Jg performance. Lower Si content is also beneficial in terms of PMOS Vt variation caused by B diffusion. However, enhanced transient charge-trapping effect (TCE) is observed from Hf-silicate with low Si content, degrading electron mobility. Hf-silicate with low Si content also shows more TCE during positive bias stress at low stress bias, which is easily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…B atoms in the dielectric can degrade reliability by producing a charge that shifts V t [9]. However, we have found that B atoms produce a charge only where SiO 2 atoms are present in HfO 2 , i.e., Hf-silicate [10]. The V t shift can be reduced by using the lowest optimal SiO 2 concentration in the HfSiO dielectric, even though more B diffusion might occur.…”
Section: Fig 2 Schematic Process Flow Of Gate Last (Or Replacement Ga...mentioning
confidence: 88%
“…B atoms in the dielectric can degrade reliability by producing a charge that shifts V t [9]. However, we have found that B atoms produce a charge only where SiO 2 atoms are present in HfO 2 , i.e., Hf-silicate [10]. The V t shift can be reduced by using the lowest optimal SiO 2 concentration in the HfSiO dielectric, even though more B diffusion might occur.…”
Section: Fig 2 Schematic Process Flow Of Gate Last (Or Replacement Ga...mentioning
confidence: 88%